Recent Updates on Biopolymers based Wound Dressings: A Review - Arora, Sonia; Nagpal, Manju; Kaur, Malkiet (Asian Journal of Chemistry, 2021)
Wound dressing is designed to support the wound bed and protect it from the factors that may delay or impede its healing such as contamination and moisture thereby facilitating and accelerate the healing process. The material used to prepare wound dressing include natural and synthetic polymer as their combination in the form of film and sponges that may be extensively used in wound dressing material. Naturally occurring polymers having many importance because of high biocompatibility and environmentally finding properties. Polysaccharides are naturally occurring polymers that have been extensively used as wound dressing materials. Homopolysaccharide are a class of polysaccharides consists of only one type of monosaccharide. Naturally occurring polymers are used for wound dressing properties because of their extracellular matrix as good acceptance by biological system. Polysaccharide is type of naturally occurring polymers that offer the advantage of good hemocompatibility and low cost in comparison with other biopolymers. The current review intends to overview the studies in which wound dressings from naturally-occurring polymers including chitosan, silk fibroin, sodium alginate and hyaluronic acid were considered.